UNDER THE INFLUENCE OF MICROBIOLOGICAL PREPARATIONSBIOTECHNOLOGY OF BELL PEPPER GROWING - Mukhayo Bafoevna Tagaeva; Islamova Mushtaribegim Ramazonovna (Web of Journals Publishing, 2025)
Information is provided on the special importance of using biological and microbiological preparations in the context of modern agricultural development under the influence of microbial preparations in greenhouses for the cultivation of vegetable melon crops, the use of microbiological preparations and growth promoters helps to increase the productivity of agricultural crops, the scientific justification of environmentally friendly farming, the use of fertilizers and pesticides, the use of advanced technologies, and the minimization of chemical means.
Keywords: TERIA-Sv, “Green, Microbial fertilizer, Amaral-F1, enzyme, soil microflora, β-glucosidase and dehydrogenase enzymes.